Prevalence and risk factors for chronic endometritis in patients with adenomyosis and infertility: a retrospective cohort study - Jingjing Li; Jiajia Wei; Saiqiong Chen; Xindan Wang; Jing Chen; Dingyuan Zeng; Li Fan (BMC, 2024)
Abstract Background To explore the incidence of chronic endometritis (CE) in patients with infertility and different forms of adenomyosis and analyze potential high-risk factors for infection. Methods This retrospective cohort study included 154 patients with infertility in the Liuzhou Maternity and Child Healthcare Hospital. Among them, 77 patients with adenomyosis were divided into four subgroups based on magnetic resonance imaging (MRI): internal, exterior, intramural, and full-thickness. Meanwhile, 77 patients did not have adenomyosis. Hysteroscopy and endometrial biopsy were performed in the proliferative phase. The main outcome measures were the morphology of the endometrium, syndecan-1 (CD138) immunohistochemical staining, clinical characteristics, and prevalence of CE in the adenomyosis subgroups. Results In comparison to the non-adenomyosis group, the adenomyosis group had significantly higher body mass index (BMI) and CA125 levels. The menstrual cycle in the adenomyosis group was significantly shorter, and menarche was significantly earlier. In comparison to the non-adenomyosis group, the adenomyosis group had a significantly higher diagnostic rate of CE (75.3% vs. 46.8% according to hysteroscopy and 74.0% vs. 33.8% according to histopathology, both with p < .050). The incidence of CE was significantly lower in patients with internal adenomyosis when compared with the other three subgroups. Increased BMI contributed to a higher risk of CE. Conclusions The prevalence of CE was significantly higher in patients with adenomyosis and infertility. The differences in the incidence of CE are closely associated with the classification of adenomyosis. When patients with infertility are diagnosed with adenomyosis, it is recommended to identify the subtype and screen for endometritis.